(Gold triangular nanoplate core)@(silver shell) nanostructures as highly sensitive and selective plasmonic nanoprobes for hydrogen sulfide detection. Issue 39 (7th October 2020) - Mi, Hua; Wang, Shengyan; Yin, Hang; Wang, Le; Mei, Lin; Zhu, Xingzhong; Zhang, Nan; Jiang, Ruibin
Abstract : AuTNP@Ag nanostructures are developed as nanoprobes for hydrogen sulfide. Owing to the high refractive index sensitivity of Au TNPs and facile sulfurization of silver, AuTNP@Ag nanostructures exhibit great sensitivity to both sulfur ions and H2 S gas. Abstract : Hydrogen sulfide plays a significant role in living beings, while its abnormal concentration is related to many diseases. Besides, H2 S gas is harmful to human beings and the environment. The detection of H2 S has therefore attracted much attention in the past several decades. Herein, highly sensitive and selective H2 S plasmonic nanoprobes (gold triangular nanoplate core)@(silver shell) (AuTNP@Ag) are reported. By virtue of the high refractive index sensitivity of Au TNPs to the surrounding medium and facile sulfurization of silver by sulfur ions, AuTNP@Ag exhibits great sensitivity to both sulfur ions and H2 S gas. The shifts of the plasmon peak are as large as 16 nm for the ventilation of 1 ppm hydrogen sulfide. AuTNP@Ag nanoprobes also exhibit very good sensing linearity at low concentrations of sulfur ions. Moreover, excellent sensing selectivity for sulfur ions is obtained. A type of test gel, which can produce a naked-eye observable color change when exposed to 1–100 ppm hydrogen sulfide gas, is developed using AuTNP@Ag nanoprobes. Owing to the high sensitivity, linearity, and selectivity of the Au TNP@Ag nanoprobes for hydrogen sulfide sensing, this work paves the way for the plasmonic detection of hydrogen sulfide in both biological and environmental applications.